Central settlements in Slovenia in 2016 - Janez Nared; David Bole; Mateja Breg Valjavec; Rok Ciglič; Maruša Goluža; Jani Kozina; Nika Razpotnik Visković; Peter Repolusk; Petra Rus; Jernej Tiran; Majda Černič Istenič (Acta Geographica Slovenica, 2017)
This article presents central settlements in Slovenia and their main characteristics in 2016. We defined central settlements based on services of general interest and the population of an individual settlement, and developed the analysis further by using competitiveness indicators. We defined 360 central settlements at six levels of centrality, among which the significance of Ljubljana as a national center of international importance and the significance of intermunicipal, local, and rural centers are increasing. The significance of certain regional centers at the second and third levels of centrality is decreasing. The level of services of general interest supplied to Slovenian territory is relatively appropriate, but it should be improved by promoting competitiveness, especially in centers of national and regional importance.